sinergitas hubungan sinergitas hubungan antara dunia usaha media,pemerintah dan LSM: sinergitas hubungan antara dunia usaha media, pemerintah dan LSM - Putri Putri; Ilham Tahier; Rani Rani; Miranti Miranti; Anghrina Ananta Sudirman; Claudya Amal Utami (RESEARCH FAIR UNISRI, 2024)
This study aims to analyze the synergy of relationships between the media industry, the government and NGOs. Synergy According to the great Indonesian dictionary, "synergy" can be defined as a joint activity or operation. Synergy can also be interpreted as a form of cooperation produced through the collaboration of each party without any feeling of defeat. Media Relations or it can also be called Media Relations is an activity to establish relationships/relations with the mass media, journalists or the press to establish cooperation and good relations by an organization, which will later affect the news or message in the mass media itself to maintain a positive impression of an organization under its auspices. According to the Great Dictionary of the Indonesian Language (KBBI), NGOs are organizational institutions that aim to fight for the interests of the community. This organization is founded by individuals or groups and is not part of the government, bureaucracy, or state, the evolution of the development paradigm, where the government is no longer the only actor in development, has implications for synergy management. The researcher seeks to recognize the role of actors and collaboration in forming collaboration in development. This study uses an exploratory research method using a qualitative approach. Through this study, the researcher wants to conduct an analysis related to the development of tourism villages based on collaborative governance. The above in the context of the research underlies the researcher's desire to investigate and describe Bank Indonesia's media relations activities in West Java through a detailed press conference conducted by Bank Indonesia. Of course, this is to build a good relationship with the media. You can improve and maintain the image of your facility. On the other hand, the implementation of collaborative governance requires effective communication to facilitate collaboration between actors so that their role in building relationships with the business world is important.